(untitled) (Revista Iberoamericana de Bioética, 2023)
Research into the social contexts of inequality due to ethnic-racial conditions is an issue which it is essential to analyse through bioethical references. This article aims to provide a basis for bioethical reflection and action in defence of ethnic and racial equality. Van Rensselaer Potter’s Global Bioethics, in a dialogue with the theoretical references of the Black movement, allows us to investigate the model of society committed to analysing global problems and motivating moral subjects to act in their localities. It is concerned with the protection of human dignity and criticises the different forms of ethnic-racial discrimination. Racism is the inferiorisation of the Other and impedes the full development of their capabilities on equal terms. The Black population has historically suffered ethnic and racial discrimination. In this regard, bioethical reflections are aimed at shedding light on this condition of inequality and bolster the social movements fighting for racial recognition and equity.